Pretrial and Its Contribution To Protection Of The Rights Of Suspectives - Sunarto; Nanda Riko Hendy Toerino (International Journal of Educational Research & Social Sciences, 2022)
People suspected of committing a crime must be respected for their human rights. To find evidence that the person suspected of committing a crime is guilty, one or several methods of coercion must be used. In upholding and respecting the human rights of alleged perpetrators of criminal acts, the process of arrest and detention must be by procedures. If not according to guidelines, pretrial efforts can be carried out. The purpose of this study was to determine whether the pretrial has provided legal benefits to the suspect's rights. The specification of this research is analytical descriptive, with normative juridical research type. Methods of data collection through collecting secondary legal materials, which include; books, laws and regulations, documents, journals, and scientific articles. Based on this research, it is found that in practice, the implementation of the pretrial trial has not been able to maximally provide legal benefits to the rights of the pretrial Petitioner. The pretrial Judge has tried to make it happen. However, if the Petitioner feels that his rights are still not protected and what is requested by the pretrial Petitioner, it is because of the facts in the Judge and the provisions in the Court. The applicable law makes the Judge unable to give a decision anymore. In addition, to provide legal benefits to the suspect as a pretrial Petitioner and then grant his request, there are still several obstacles or obstacles, including not fully understanding the meaning, scope, and existence of this pretrial. Put forward other facts that can be taken into consideration by pretrial judges in making decisions. In addition, some pretrial judges are less thorough in examining what things will be requested or requested in the submission and pretrial examination.